Anti-UV hydrolysis-resistant PET functional master batch and preparation method thereof

By preparing UV-resistant and hydrolysis-resistant PET functional masterbatch through specific ratios and complex chemical reactions, the problem of uneven UV resistance and hydrolysis resistance of PET materials is solved, achieving a high-efficiency improvement in UV resistance and hydrolysis resistance, which is suitable for packaging, electronics, photovoltaics, automobiles and medical devices.

CN120865523APending Publication Date: 2025-10-31JIANGSU SHUANGXING COLOR PLASTIC NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895535.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-22
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In the existing technology, PET materials have compatibility and dispersibility problems in terms of UV resistance and hydrolysis resistance. Especially in the film manufacturing process, anti-hydrolysis agents and UV absorbers are prone to agglomeration or uneven distribution due to stretching, resulting in uneven performance. In addition, the production cost is high and the process is highly dependent.

Method used

UV-resistant and hydrolysis-resistant PET functional masterbatch is prepared using raw materials with specific ratios and complex chemical reaction processes. It includes terephthalic acid, ethylene glycol, isophorone diester, 2,4-dihydroxybenzoic acid, etc. Polymer chains are formed through esterification and polycondensation reactions. Beta molecular sieve and zinc metaborate are added to improve dispersibility and light stability.

Benefits of technology

It significantly improves the UV resistance and hydrolysis resistance of PET products, ensuring stability in high temperature and high humidity environments, and meeting the application needs of packaging, electronics, photovoltaics, automotive and medical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201730920000051
    Figure BDA0005201730920000051
  • Figure BDA0005201730920000061
    Figure BDA0005201730920000061
  • Figure BDA0005201730920000062
    Figure BDA0005201730920000062
Patent Text Reader

Abstract

The invention discloses an anti-UV hydrolysis-resistant PET functional master batch and a preparation method thereof, UV absorbing groups such as isophorone diester and 2, 4-dihydroxybenzoic acid are introduced to enhance the UV resistance, and neopentyl glycol and trimethylolpropane are introduced to enhance the hydrolysis resistance of a molecular chain. Besides, the Beta molecular sieve, the zinc metaborate and other auxiliaries are utilized, so that the uniform distribution of the light stabilizer and the ultraviolet light absorber in the molecular structure is improved, and the problem that the UV absorption performance and the hydrolysis resistance of the film are not uniform due to molecular arrangement change in the stretching process is effectively avoided. The ultraviolet resistance, the strength and the hydrolysis resistance of the film are improved through the synergistic effect of all the components in the formula, so that the application requirements of PET products in the fields of packaging, electronics, photovoltaics, automobiles, medical instruments and the like are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer material preparation technology, specifically relating to a UV-resistant and hydrolysis-resistant PET functional masterbatch and its preparation method. Background Technology

[0002] UV-resistant and hydrolysis-resistant PET functional masterbatches play an increasingly important role in modern industry. Besides electronics, photovoltaics, and high-performance packaging, these masterbatches are also widely used in automotive interiors, outdoor billboards, and medical devices, providing durable protection and aesthetics. These masterbatches combine the excellent properties of PET materials with key performance characteristics such as UV resistance and hydrolysis resistance, providing long-lasting protection for various applications. For example, in the packaging field, some applications requiring UV resistance need to block all UVA ultraviolet rays at 400nm and below, ensuring that the materials inside the packaging are not subject to fading or aging due to long-term UV exposure. In the electronics or photovoltaic fields, some applications need to remain stable under high temperature and humidity environments, resisting hydrolysis reactions and thus extending product lifespan.

[0003] In existing technologies, the UV resistance and hydrolysis resistance of PET are generally improved by adding anti-hydrolysis agents and UV absorbers. Common anti-hydrolysis agents include carbodiimide and oxazoline, while UV absorbers include o-hydroxybenzophenones and benzotriazoles. However, in practical applications, there are issues with the compatibility and dispersibility of anti-hydrolysis agents and UV absorbers. For example, when dispersing anti-hydrolysis agents and UV absorbers in the PET matrix using nanodispersion technology, it is necessary to avoid mutual interference and agglomeration. In addition, uniformly dispersing nanomaterials into the matrix is ​​also difficult, especially during the manufacturing process of PET films and other products. Film stretching may change the molecular arrangement, causing the anti-hydrolysis agent and UV absorber nanoparticles originally dispersed in the matrix to change their position with stretching, which may lead to re-aggregation or uneven distribution of nanoparticles.

[0004] Common solutions to compatibility and dispersibility issues include surface modification of nanoparticles to increase their affinity with the PET matrix, thereby improving dispersibility and compatibility. Advanced blending techniques, such as melt blending and solution blending, are also employed to ensure uniform dispersion of anti-hydrolysis agents and UV absorbers within the PET matrix. However, these solutions are highly dependent on processes and equipment, resulting in high production costs, and it is difficult to tailor production processes for different products.

[0005] Therefore, improving the UV resistance and hydrolysis resistance of PET products has become an urgent problem to be solved in the field of polymer material preparation technology. This invention addresses this problem by proposing a PET functional masterbatch with excellent UV resistance and hydrolysis resistance, and its preparation method. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a UV-resistant and hydrolysis-resistant PET functional masterbatch and its preparation method, so as to reduce or avoid the problems mentioned above.

[0007] To address the aforementioned technical problems, this invention proposes a UV-resistant and hydrolysis-resistant PET functional masterbatch, prepared from the following raw materials in parts by weight: terephthalic acid: 95-105 parts by weight; ethylene glycol: 60-70 parts by weight; isophorone diester: 20-30 parts by weight; 2,4-dihydroxybenzoic acid: 10-18 parts by weight; titanium tetrachloride: 0.05-0.10 parts by weight; antimony acetate: 0.04-0.08 parts by weight; phosphoric acid: 0.03-0.06 parts by weight; 2,6-di-tert-butyl-p-cresol: 0.03-0.08 parts by weight; zinc metaborate: 0.01-0.03 parts by weight; diethylene glycol: 3-7 parts by weight; neopentyl glycol: 8-12 parts by weight; beta molecular sieve: 8-12 parts by weight; trimethylolpropane (TMP): 3-6 parts by weight.

[0008] This invention also proposes a method for preparing the above-mentioned functional masterbatch, comprising the following steps: In an esterification tank, terephthalic acid, ethylene glycol, 2,4-dihydroxybenzoic acid, diethylene glycol, and neopentyl glycol are weighed and added sequentially. The added materials are stirred evenly, and then the temperature is raised to 150°C. Titanium tetrachloride is then added as a catalyst. Nitrogen gas is introduced under normal pressure to purge air from the esterification tank, gradually reducing the pressure to 0.5 MPa. The esterification reaction is carried out under nitrogen protection for 6-8 hours, with the reaction temperature controlled at 190-220°C. With 60 minutes remaining in the esterification reaction time, trimethylolpropane is added to a stainless steel esterification tank and stirred evenly using a mechanical stirrer. With 30 minutes remaining in the esterification reaction time, Beta molecular sieve is added to the esterification tank. After the esterification reaction is completed, the temperature inside the esterification tank is lowered to 220°C. Phosphoric acid is added according to the formula ratio while maintaining nitrogen protection. Stir for 5-10 minutes to ensure uniform distribution of phosphoric acid; gradually increase the temperature in the esterification tank to 230℃-250℃, adjust the pressure in the tank to 500-1000Pa, add antimony acetate as a polycondensation catalyst according to the formula ratio, and add isophorone diester; maintain a nitrogen protection atmosphere and a pressure of 500-1000Pa, and continue the pre-polymerization reaction in the esterification tank for 3-5 hours; after the pre-polymerization reaction is completed, transfer the pre-polymerization product from the esterification tank to the polycondensation tank, and simultaneously add 2,6-di-tert-butyl-p-cresol and zinc metaborate; reduce the pressure in the polycondensation tank to 10-50Pa; then gradually increase the temperature to 280℃-290℃ and carry out the polycondensation reaction for 2-3 hours, while continuously stirring with a mechanical stirrer in the stainless steel polycondensation tank; when the polymer molecular weight reaches 35,000-45,000 g / mol, the polycondensation reaction is considered complete.

[0009] Preferably, the method further includes: introducing polyester melt from a polycondensation tank into a twin-screw extruder, extruding and cooling it to form strips; and then pelletizing it after cooling.

[0010] This invention enhances UV resistance by introducing UV-absorbing groups such as isophorone diester and 2,4-dihydroxybenzoic acid, while simultaneously improving the hydrolysis resistance of the molecular chain by introducing neopentyl glycol and trimethylolpropane. Furthermore, the use of Beta molecular sieves, zinc metaborate, and other additives improves the uniform distribution of light stabilizers and UV absorbers in the molecular structure, effectively preventing uneven UV absorption and hydrolysis resistance caused by changes in molecular arrangement during film stretching. The synergistic effect of the components in the formulation improves the film's UV resistance, strength, and hydrolysis resistance, thus meeting the application requirements of PET products in packaging, electronics, photovoltaics, automotive, and medical devices. Detailed Implementation

[0011] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, the specific embodiments of the present invention will now be described in detail.

[0012] To address the issues with UV resistance and hydrolysis resistance in PET products, this invention functionally modifies polyethylene terephthalate (PET) to prepare a specialized functional masterbatch suitable for PET products. Through this invention and its preparation method, the UV resistance and hydrolysis resistance of PET products can be significantly improved, while also enhancing the material's mechanical strength and thermal stability, thereby meeting the application requirements of PET products in packaging, electronics, construction, and other fields.

[0013] Specifically, this invention proposes a UV-resistant and hydrolysis-resistant PET functional masterbatch, which can be used as a raw material for preparing PET products, for example, as the sole raw material for preparing PET products, or as a partial raw material for preparing PET products, and can be combined with other raw materials to prepare the desired PET products.

[0014] In one specific embodiment, the UV-resistant and hydrolysis-resistant PET functional masterbatch of the present invention is prepared from the following raw materials in parts by weight: terephthalic acid (PTA): 95-105 parts by weight; ethylene glycol (EG): 60-70 parts by weight; isophorone diester (IPDE): 20-30 parts by weight; 2,4-dihydroxybenzoic acid (2,4-DHBA): 10-18 parts by weight; titanium tetrachloride (TiCl4): 0.05-0.10 parts by weight; antimony acetate (… Sb₂O₃: 0.04-0.08 parts by weight; Phosphoric acid (H₃PO₄): 0.03-0.06 parts by weight; 2,6-Di-tert-butyl-p-cresol (BHT): 0.03-0.08 parts by weight; Zinc metaborate: 0.01-0.03 parts by weight; Diethylene glycol (DEG): 3-7 parts by weight; Neopentyl glycol (NPG): 8-12 parts by weight; Beta molecular sieve: 8-12 parts by weight; Trimethylolpropane (TMP): 3-6 parts by weight.

[0015] In this process, PTA, as the main diacid component of the polyester, provides a stable structure for the main chain. EG provides the diols required for the reaction, regulating the flexibility and viscosity of the polyester molecules. IPDE improves mechanical properties and thermal stability by introducing rigid groups, while also assisting in enhancing UV resistance. 2,4-DHBA, as a UV-absorbing component, participates in the copolymerization of the polyester chain through its hydroxyl and carboxyl groups. Neopentyl glycol (NPG) replaces part of ethylene glycol, providing a more stable alcohol component and significantly improving the hydrolysis resistance of the polyester chain. Trimethylolpropane (TMP) is introduced as a crosslinking monomer, improving the steric stability of the molecular chain and enhancing hydrolysis resistance. TiCl4 acts as a catalyst in the esterification stage, promoting rapid esterification. Sb₂O₃ acts as a catalyst in the polymerization stage, used to increase the polymerization rate and molecular weight. H₃PO₄ is used to stabilize the polyester chain structure and suppress side reactions. BHT is used to inhibit oxidative degradation of the material at high temperatures. Zinc metaborate is used to improve the thermal stability of the film during high-temperature stretching. DEG acts as an auxiliary solvent, helping to regulate the viscosity of the reaction and preventing premature polymer precipitation. Xylene is used to improve mixing in the early stages of the reaction and to help evaporate byproduct water. Beta molecular sieves are a type of nanoscale molecular sieve with a 12-membered ring cross-channel structure, used to ensure efficient dehydration in esterification reactions. At the same time, their unique cageless three-dimensional channel structure facilitates the diffusion of reactant and product molecules and also has shape-selective catalysis effects.

[0016] The raw materials of this invention involve a complex chemical reaction process, mainly including the reaction of the ester groups of IPDE with the carboxyl groups of PTA to generate polyester chains; the hydroxyl groups in NPG undergo esterification with the carboxyl groups of terephthalic acid (PTA) or 2,4-dihydroxybenzoic acid (2,4-DHBA) to form monoesters or diesters; the three hydroxyl groups of TMP undergo esterification with the carboxyl groups of PTA or 2,4-DHBA to gradually generate monoesters, diesters, and trimers. Next, the carboxyl groups of DHBA undergo esterification with the hydroxyl groups of EG to generate esterified monomers, providing precursors for subsequent polymerization reactions. Then, the ester groups of IPDE react with the carboxyl groups of DHBA to form copolymers. Finally, all the above intermediates are mixed and polymerized together with EG to form PET polymer chains.

[0017] IPDE, possessing two ester groups, can undergo esterification reactions with PTA and EG. Furthermore, the ester groups of IPDE can react with the carboxyl groups in PTA and the hydroxyl groups in EG to form long-chain polyesters. The introduction of IPDE contributes to the rigidity of the molecular chain and a certain degree of UV absorption. DHBA, being an aromatic compound containing phenolic hydroxyl groups, allows its carboxyl groups to esterify with EG and PTA, while its phenolic hydroxyl groups can copolymerize with IPDE through esterification. Simultaneously, the presence of phenolic hydroxyl groups provides functional groups for UV absorption.

[0018] Furthermore, the UV-resistant and hydrolysis-resistant PET functional masterbatch of the present invention can be prepared by the following method.

[0019] Specifically, the method includes the following steps: First, in a stainless steel esterification tank, terephthalic acid, ethylene glycol, 2,4-dihydroxybenzoic acid, diethylene glycol, and neopentyl glycol are weighed and added sequentially. The added materials are stirred evenly using a mechanical stirring device in the stainless steel esterification tank, and then the temperature is raised to 150°C. Then, titanium tetrachloride is added as a catalyst, and nitrogen gas is introduced under normal pressure to expel air from the esterification tank, gradually reducing the pressure to 0.5 MPa. The esterification reaction is carried out under nitrogen protection for 6-8 hours, and the reaction temperature is controlled at 190-220°C. During the esterification reaction, the by-product water generated by the esterification reaction is evaporated and condensed and discharged through a condenser connected to the top of the stainless steel esterification tank.

[0020] With 60 minutes remaining in the esterification reaction, trimethylolpropane is added to the stainless steel esterification tank and stirred evenly using a mechanical stirrer within the tank to prevent uneven TMP reaction that could affect the system viscosity.

[0021] With 30 minutes remaining in the esterification reaction, add Beta molecular sieves to the stainless steel esterification tank. Simultaneously, check if the condenser is no longer collecting moisture to determine that the esterification reaction is complete. Reduce the temperature inside the esterification tank to 220°C. Under nitrogen protection, add phosphoric acid according to the formula ratio. Stir for 5-10 minutes using the mechanical stirrer in the stainless steel esterification tank to ensure uniform distribution of phosphoric acid.

[0022] The temperature inside the esterification tank is gradually increased to 230℃-250℃, and the pressure inside the tank is adjusted to 500-1000Pa. With the stirring of the mechanical stirring device, antimony acetate is added as a polycondensation catalyst according to the formula ratio, and isophorone diester is added. Under nitrogen protection and pressure of 500-1000Pa, the pre-polycondensation reaction is continued in the esterification tank for 3-5 hours.

[0023] After the pre-polymerization reaction is complete, the pre-polymerization product is transferred from the stainless steel esterification tank to the stainless steel polymerization tank, and 2,6-di-tert-butyl-p-cresol and zinc metaborate are added simultaneously. The pressure inside the polymerization tank is reduced to 10-50 Pa using a connected vacuum system. The temperature is then gradually increased to 280℃-290℃, and the polymerization reaction is carried out for 2-3 hours. The reaction is continuously stirred using a mechanical stirrer inside the polymerization tank. The polymerization reaction is considered complete when the polymer molecular weight reaches 35,000-45,000 g / mol. Because TMP introduces branching points, the viscosity of the system increases during the polymerization reaction. Therefore, it is necessary to gradually increase the temperature and maintain stirring to prevent localized gelation.

[0024] The polyester melt is fed from the polycondensation tank into a twin-screw extruder, where it is extruded and cooled to form a long strip. The strip is then rapidly cooled by a water cooling system and granulated into pellets with a diameter of 2-4 mm using a pelletizer.

[0025] The performance of the PET film prepared from the PET functional masterbatch of the present invention will be described in detail below through specific embodiments 1-6.

[0026] For ease of explanation, the raw materials of PET functional masterbatch are represented in alphabetical order.

[0027] A: Terephthalic acid (PTA); B: Ethylene glycol (EG); C: Isophorone diester (IPDE); D: 2,4-Dihydroxybenzoic acid (2,4-DHBA); E: Titanium tetrachloride (TiCl4); F: Antimony acetate (Sb2O3); G: Phosphoric acid (H3PO4); H: 2,6-Di-tert-butyl-p-cresol (BHT); I: Zinc metaborate; J: Diethylene glycol (DEG); K: Neopentyl glycol (NPG); L: Beta molecular sieve; M: Trimethylolpropane (TMP).

[0028] The following table lists the weight parts of each component of the PET functional masterbatch in Examples 1-6.

[0029] Example 1 2 3 4 5 6 A 95 105 95 100 100 100 B 65 75 70 75 65 70 C 25 35 30 25 35 30 D 15 25 20 25 20 15 E 0.05 0.1 0.07 0.08 0.06 0.07 F 0.04 0.08 0.06 0.08 0.05 0.06 G 0.03 0.06 0.05 0.06 0.04 0.05 H 0.03 0.08 0.06 0.07 0.05 0.06 I 0.01 0.03 0.02 0.03 0.02 0.03 J 3 7 5 6 4 5 K 8 9 10 10 3 12 L 8 12 10 11 9 10 M 3 4 4 5 5 6

[0030] The table below shows the performance parameters of PET films prepared using the PET functional masterbatches from Examples 1-6.

[0031]

[0032] The performance parameters are analyzed as follows: (1) UV resistance. 2,4-Dihydroxybenzoic acid (2,4-DHBA) and isophorone diester (IPDE) provide efficient UV absorption capacity, with absorption peaks covering the UV-A and UV-B ranges. Beta molecular sieves adsorb some UV radiation through pore distribution, further reducing UV transmittance. (2) Strength performance. The optimization of the PTA and EG ratio provides a balance between rigidity and flexibility of the main chain. The rigid structure of isophorone diester (IPDE) significantly improves tensile strength. In the 3μm-8μm range, the strength performance is superior. (3) Thermal stability. The synergistic effect of phosphoric acid and BHT inhibits high-temperature degradation and improves the thermal stability of the film. The isophorone group further enhances the mechanical properties at high temperatures. (4) Hydrolysis resistance. The introduction of neopentyl glycol (NPG) and trimethylolpropane (TMP) enhances the crosslinking degree of the molecular chain and hydrolysis resistance, ensuring stability in humid and hot environments.

[0033] In summary, Examples 1-6 demonstrated the potential for optimizing UV resistance and hydrolysis resistance by fine-tuning the raw material ratios and varying the film thickness, while ensuring a balance between strength and thermal stability.

[0034] To conduct performance comparisons, this invention designed comparative examples 1-6. The design concept of the comparative examples is as follows: omit certain key components (such as IPDE, 2,4-DHBA, Beta molecular sieve, etc.) and test UV absorption or hydrolysis resistance parameters; or replace certain components (such as replacing IPDE with a traditional plasticizer or BHT with a conventional antioxidant) and test mechanical properties or thermal stability parameters; or retain the basic components (PTA and EG) to ensure copolymerization and test the performance degradation due to the absence of functional components.

[0035] The adopted measures are shown in the table below.

[0036]

[0037] The table below shows the performance parameters of the PET films in Comparative Examples 1-6, and the reasons for the performance degradation are listed in the corresponding treatment methods of the comparative examples.

[0038]

[0039] In the table above, the comparative examples are processed as follows: Comparative Example 1 omits IPDE and 2,4-DHBA compared to Example 1; Comparative Example 2 replaces IPDE with phthalate compared to Example 2; Comparative Example 3 omits Beta molecular sieve and Sb2O3 compared to Example 3; Comparative Example 4 replaces TMP with silane coupling agent compared to Example 4; Comparative Example 5 omits NPG and EMP compared to Example 5; Comparative Example 6 omits H3PO4 compared to Example 6. Apart from the above differences, the remaining components and weight parts of each comparative example and its corresponding example remain unchanged.

[0040] A performance comparison between Comparative Examples 1-6 and Examples 1-6 reveals that the UV transmittance of the films in the comparative examples is significantly increased, mainly due to the absence or substitution of IPDE and 2,4-DHBA, and the omission of Beta molecular sieve. In the examples, IPDE provides excellent UV absorption, 2,4-DHBA enhances UV resistance, and Beta molecular sieve further improves overall barrier properties. Furthermore, the strength of the comparative examples is reduced, especially when IPDE is omitted or a flexible plasticizer is used as a substitute; insufficient molecular chain rigidity leads to decreased mechanical properties. Moreover, the hydrolysis resistance of the comparative examples is lower than that of the examples, primarily due to the omission of NPG and EMP or the use of substitutes. H3PO4 and BHT synergistically stabilize the molecular chains at high temperatures in the examples. Additionally, the hydrolysis resistance of the comparative examples is significantly reduced because Beta molecular sieve and zinc metaborate are omitted. These two components significantly enhance barrier properties in the examples through physical filling and interfacial adsorption.

[0041] By comparing the comparative examples and the embodiments above, the following conclusions can be drawn: the functional components in the embodiments (such as IPDE, 2,4-DHBA, Beta molecular sieve, NPG, and EMP) significantly contribute to UV resistance, strength, and hydrolysis resistance. The performance parameters of the comparative example films showed a significant decrease after key components were omitted or replaced, demonstrating the necessity and superiority of the optimized formulation and unique design of the embodiment combinations.

[0042] In summary, the PET functional masterbatch of this invention significantly overcomes the limitations of PET products in terms of UV resistance and hydrolysis resistance by optimizing the molecular structure and the combination of functional components. By introducing UV-absorbing groups such as isophorone diester (IPDE) and 2,4-dihydroxybenzoic acid (2,4-DHBA), the absorption capacity of the molecular chain for ultraviolet light is enhanced, while simultaneously improving the film's aging resistance. Furthermore, the use of Beta molecular sieves, zinc metaborate, and other additives improves the uniform distribution of light stabilizers and UV absorbers in the molecular structure, effectively preventing uneven UV absorption performance caused by changes in molecular arrangement during film stretching. The synergistic effect of components such as NPG and EMP in the formulation not only enhances the film's UV resistance, strength, and hydrolysis resistance but also ensures the uniformity of film performance, providing an innovative material solution for the preparation of high-performance PET products.

[0043] Those skilled in the art should understand that although the present invention has been described with reference to multiple embodiments, not every embodiment contains only one independent technical solution. This description is provided merely for clarity; those skilled in the art should understand the specification as a whole and consider the technical solutions involved in each embodiment as being able to be combined with each other to form different embodiments to understand the scope of protection of the present invention.

[0044] The above description is merely an illustrative embodiment of the present invention and is not intended to limit the scope of the invention. Any equivalent changes, modifications, and combinations made by those skilled in the art without departing from the concept and principles of the present invention should fall within the scope of protection of the present invention.

Claims

1. A UV-resistant and hydrolysis-resistant PET functional masterbatch, characterized in that, The UV-resistant and hydrolysis-resistant PET functional masterbatch is prepared from the following raw materials in parts by weight: terephthalic acid: 95-105 parts by weight; ethylene glycol: 60-70 parts by weight; isophorone diester: 20-30 parts by weight; 2,4-dihydroxybenzoic acid: 10-18 parts by weight; titanium tetrachloride: 0.05-0.10 parts by weight; antimony acetate: 0.04-0.08 parts by weight; phosphoric acid: 0.03-0.06 parts by weight; 2,6-di-tert-butyl-p-cresol: 0.03-0.08 parts by weight; zinc metaborate: 0.01-0.03 parts by weight; diethylene glycol: 3-7 parts by weight; neopentyl glycol: 8-12 parts by weight; beta molecular sieve: 8-12 parts by weight; trimethylolpropane (TMP): 3-6 parts by weight.

2. A method for preparing the functional masterbatch as described in claim 1, characterized in that, The method includes the following steps: In an esterification tank, terephthalic acid, ethylene glycol, 2,4-dihydroxybenzoic acid, diethylene glycol, and neopentyl glycol are weighed and added sequentially. The added materials are stirred evenly, and then the temperature is raised to 150°C. Titanium tetrachloride is then added as a catalyst. Nitrogen gas is introduced under normal pressure to purge air from the esterification tank, gradually reducing the pressure to 0.5 MPa. The esterification reaction is carried out under nitrogen protection for 6-8 hours, with the reaction temperature controlled at 190-220°C. With 60 minutes remaining in the esterification reaction time, trimethylolpropane is added to a stainless steel esterification tank and stirred evenly using a mechanical stirrer. With 30 minutes remaining in the esterification reaction time, Beta molecular sieve is added to the esterification tank. After the esterification reaction is completed, the temperature inside the esterification tank is lowered to 220°C. Phosphoric acid is added according to the formula ratio while maintaining nitrogen protection. The mixture is stirred for 5-10 minutes. To ensure uniform distribution of phosphoric acid, the temperature inside the esterification tank is gradually increased to 230℃-250℃, and the pressure inside the tank is adjusted to 500-1000Pa. Antimony acetate is added as a polycondensation catalyst according to the formula ratio, along with isophorone diester. Under nitrogen protection and a pressure of 500-1000Pa, the pre-polymerization reaction continues in the esterification tank for 3-5 hours. After the pre-polymerization reaction is completed, the pre-polymerization product is transferred from the esterification tank to the polycondensation tank, and 2,6-di-tert-butyl-p-cresol and zinc metaborate are added. The pressure inside the polycondensation tank is reduced to 10-50Pa. Then, the temperature is gradually increased to 280℃-290℃, and the polycondensation reaction is carried out for 2-3 hours. The reaction is continuously stirred by a mechanical stirrer inside the stainless steel polycondensation tank. The polycondensation reaction is considered complete when the polymer molecular weight reaches 35,000-45,000 g / mol.

3. The method as described in claim 2, characterized in that, The method further includes: introducing polyester melt from a polycondensation tank into a twin-screw extruder, extruding and cooling it to form strips; and then pelletizing it after cooling.